Stratigraphy and evolution of the buried CO2 deposit in the Martian south polar cap. Issue 9 (10th May 2016) - Bierson, C. J.; Phillips, R. J.; Smith, I. B.; Wood, S. E.; Putzig, N. E.; Nunes, D.; Byrne, S.
Abstract: Observations by the Shallow Radar instrument on Mars Reconnaissance Orbiter reveal several deposits of buried CO2 ice within the south polar layered deposits. Here we present mapping that demonstrates this unit is 18% larger than previously estimated, containing enough mass to double the atmospheric pressure on Mars if sublimated. We find three distinct subunits of CO2 ice, each capped by a thin (10–60 m) bounding layer (BL). Multiple lines of evidence suggest that each BL is dominated by water ice. We model the history of CO2 accumulation at the poles based on obliquity and insolation variability during the last 1 Myr assuming a total mass budget consisting of the current atmosphere and the sequestered ice. Our model predicts that CO2 ice has accumulated over large areas several times during that period, in agreement with the radar findings of multiple periods of accumulation. Key Points: Mars' south polar cap contains a deposit with enough CO2 to double the atmospheric pressure if it sublimated Surface and radar observations show this deposit to be three CO2 subunits capped by water ice Modeling allows us to constrain the minimum age of this deposit to be ∼300 kyr old